PERENCANAAN TEBAL PERKERASAN LENTUR (FLEXIBLE PAVEMENT) DENGAN METODE MDP 2017 DAN AASHTO 1993 (STUDI KASUS JALAN BANTENG KOTA PALANGKA RAYA) - Berutu, Maspriadi (Universitas Muhammadiyah Surabaya, 2023)
Roads serve as infrastructure for land traffic, pedestrian crossings, and other uses. The auxiliary structures and equipment for traffic that are at ground level, above ground level, below ground level, and/or above water level, with the exception of railroads, lorry roads, and cable roads, are the subject of the discussion. In this planning, the MDP 2017 and AASHTO 1993 methods are used. This study required field CBR and Daily Traffic Volume (LHR) data. Road segment CBR data was obtained at 6.423% from DCP testing at the study site. Daily traffic volume 1914 SMP. The results of analysis and calculation, obtained pavement thickness with the MDP 2017 method is 315 mm with surface layer details of 65 mm, bottom foundation layer 250 mm. While the thickness of pavement with the AASHTO 1993 method is 340 mm with surface layer details of 130 mm, top foundation layer 105 mm and bottom foundation layer 105 mm.